Los narradores deportivos y sus epopeyas cotidianas - Federico Medina Cano (Estudios sobre las Culturas Contemporáneas)
Narrators are an important part of a sports show. They reconstruct what is going on the field with a decorative language that has its own poetique and baroque style. This language is full of parallels and it explores the possibilities of metaphor. These commentators are part of an oral tradition. Sports narrators bring oral narration alive; and with emotivity and affectivity, they preserve and enrich the art of narration. This article analyzes the roots of these new epic stories, the subcodes that give form to their poetic, and the fonns given to a baroque style in narration.